2012
DOI: 10.5121/ijma.2012.4201
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Colour as an Attribute that Intensifies User's Engagement in Game Plays

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Schreiber (2011) said that storyline should be considered by game designers since it was the narrative thread of the game. It should also be clearly stated at the beginning to the end of the game (Martinez et al, 2012). Another integral part of a game was reward system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Schreiber (2011) said that storyline should be considered by game designers since it was the narrative thread of the game. It should also be clearly stated at the beginning to the end of the game (Martinez et al, 2012). Another integral part of a game was reward system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martinez, Adi, and Prima (2012) specifically identified that colors are one of the key features of aesthetics and one of the important aspects in designing a popular game. Distinctive colors and color situations were important tools in game development that could stimulate excitement and could make a game more realistic.…”
Section: Literature Reviewmentioning
confidence: 99%